A Critical Review of the Nigerian Entrepreneurial Ecosystem:Understanding and Leveraging the Opportunities - Wahab, Fatai Kayode; Akintade, Elizabeth Abidemi; Abdulmajeed, Tajudeen Idera (Journal of Business Management and Accounting, 2026)
The Nigerian entrepreneurial ecosystem is a dynamic yet complex framework that influences economic diversification and development. Despite the immense potential of the Nigerian economy, the ecosystem faces systemic challenges that hinder its effectiveness. Institutional voids, inadequate infrastructure, limited access to finance, a widening skills gap, regulatory bottlenecks, and restricted market access collectively impede entrepreneurial growth and economic transformation in the country. This study adopts a systematic review approach to analyse the Nigerian entrepreneurial ecosystem by examining its key components, identifying prevailing challenges, and exploring strategies to leverage its potential. Drawing on an extensive review of scholarly literature, policy documents, and empirical studies, the study addresses the existing gap in understanding the interplay among the ecosystem’s core elements. The study reveals the pivotal role of government policies, financial institutions, digital infrastructure, and market linkages in shaping entrepreneurial outcomes. The findings emphasise the need for targeted interventions, including policy reforms, capacity-building initiatives, public–private partnerships, and improved access to funding, as essential steps towards bridging existing gaps and unlocking the full potential of Nigerian entrepreneurial ecosystem.